Harmonise the Open Access to Scholarly Communication - Shetty, Veda L; H L, Yashashwini. (International Journal of Information Studies, 2025)
Open access to the world's scientific and technological information is a worthy goal for the library profession. Scholarly communication occurs through journals, conferences, and articles daily. The open access movement supports students, the academic community, and citizens of industries and their professional development. Users require timely and affordable access to the information to frame their research questions, design their approaches, and verify their results. As Librarians, we must facilitate these functions. Open access is one vital approach. In the past, we had focused on elevating awareness of open access to scientific and technological information. This paper highlights a more open society through better access to information